Facilitators’ views on content goals, learning obstacles, and teaching resources in reference to conditional probability - Griese, Birgit; Nieszporek, Ralf; Biehler, Rolf

Mathematik-Vorkurse zur Vorbereitung auf das Studium – Zielsetzungen und didaktische Konzepte - Lankeit, Elisa; Biehler, Rolf (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

The role of learning strategies for performance in mathematics courses for engineers - Liebendörfer, Michael; Göller, Robin; Gildehaus, Lara; Kortemeyer, Jörg; Biehler, Rolf; Hochmuth, Reinhard; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse

Data Science, Statistics, and Civic Statistics: Education for a Fast Changing World - Ridgway, Jim; Campos, Pedro; Biehler, Rolf (Statistics for Empowerment and Social Engagement)

Mini-Aufgaben in mathematischen Übungsgruppen zur Analysis: Charakteristika von Aufgaben und Abstimmungsverhalten von Studierenden - Bauer, Thomas; Biehler, Rolf; Lankeit, Elisa (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Vorkurse und ihre Wirkungen im Übergang Schule – Hochschule - Lankeit, Elisa; Biehler, Rolf (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Enriching videos with interactive questions to enhance students’ cognitive activity: concept and implementation - Liebendörfer, Michael; Profeta, Angelo; Krämer, Sandra; Schlüter, Sarah; Becher, Silvia; Biehler, Rolf; Mai, Tobias; Schmitz, Angela

Dokumentation der Erhebungsinstrumente des Projekts WiGeMath - Schürmann, Mirko; Büdenbender-Kuklinski, C.; Lankeit, Elisa; Liebendörfer, Michael; Hochmuth, R.; Biehler, Rolf; Schaper, N.

Einführung in das WiGeMath-Projekt: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schürmann, Mirko (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Ein Rahmenmodell für hochschuldidaktische Maßnahmen in der Mathematik - Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Schaper, Niclas; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schürmann, Mirko (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

Jupyter Notebooks for Teaching, Learning, and Doing Data Science - Fleischer, Yannik; Hüsing, Sven; Biehler, Rolf; Podworny, Susanne; Schulte, Carsten (Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference on Teaching Statistics)
We report on our work with students in our data science courses, focusing on the analysis of students’ results. This study represents an in-depth analysis of students’ creation and documentation of machine learning models. The students were supported by educationally designed Jupyter Notebooks, which are used as worked examples. Using the worked example, students document their results in a so-called computational essay. We examine which aspects of creating computational essays are difficult for students to find out how worked examples should be designed to support students without being too prescriptive. We analyze the computational essays produced by students and draw consequences for redesigning our worked example.

Profession-Specific Curriculum Design in Mathematics Teacher Education: Connecting Disciplinary Practice to the Learning of Group Theory - Wessel, Lena; Leuders, Timo (Practice-Oriented Research in Tertiary Mathematics Education)

Civic Statistics for Prospective Teachers: Developing Content and Pedagogical Content Knowledge Through Project Work - Podworny, Susanne; Frischemeier, Daniel; Biehler, Rolf (Statistics for Empowerment and Social Engagement)

Data Visualization Packages for Non-inferential Civic Statistics in High School Classrooms - Frischemeier, Daniel; Podworny, Susanne; Biehler, Rolf (Statistics for Empowerment and Social Engagement)

An example of rich, real and multivariate survey data for use in school - Podworny, Susanne; Fleischer, Yannik; Stroop, Dietlinde; Biehler, Rolf

From private digital platforms to public data spaces: implications for the digital transformation - Beverungen, Daniel; Hess, Thomas; Köster, Antonia; Lehrer, Christiane (Electronic Markets)
Technological developments such as Cloud Computing, the Internet of Things, Big Data and Artificial Intelligence continue to drive the digital transformation of business and society. With the advent of platform-based ecosystems and their potential to address complex challenges, there is a trend towards greater interconnectedness between different stakeholders to co-create services based on the provision and use of data. While previous research on digital transformation mainly focused on digital transformation within organizations, it is of growing importance to understand the implications for digital transformation on different layers (e.g., interorganizational cooperation and platform ecosystems). In particular, the conceptualization and implications of public data spaces and related ecosystems provide promising research opportunities. This special issue contains five papers on the topic of digital transformation and, with the editorial, further contributes by providing an initial conceptualization of public data spaces' potential to foster innovative progress and digital transformation from a management perspective.
Keywords: Digital transformation; Public data spaces; Digital platforms; GAIA-X

Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Platform; Text mining; Machine learning; Data communications; Interpretive research; Systems design and implementation

Self-regulated learning in a mathematics course for engineers in the first semester: insights into students reported resource management and cognitive strategies - Kolbe, Tim; Wessel, Lena (Fourth conference of the International Network for Didactic Research in University Mathematics)

Mahr, Melanie: Reden ist Gold... – vom Umgang mit Sexualität bei Jugendlichen. Eine empirisch-qualitative Studie zur Situation der Sexualpädagogik im Kontext katholischer, vollstationärer Einrichtungen der Kinder- und Jugendhilfe. – Würzburg: Echter Verlag 2020 (=Studien zur Theologie und Praxis der Caritas und Sozialen Pastoral, 40) - Reis, Oliver (Theologische Revue)

Wann ist eine Differenz diskriminierend? Das Oszillieren zwischen Unterschieden und Ungleichheiten in der katholischen Gemeindearbeit - Hofmeister, Lisa; Reis, Oliver (Der Vielfalt Raum geben. Zum ambivalenten Potenzial einer differenzsensiblen Kirche)

Wie steht es mit der Situationsorientierung der Religionspädagogik? - Mellentin, Franziska; Reis, Oliver (unterwegs 2/2022)

Schulbuch - Rakowski, Jana; Reis, Oliver (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Vorlesen - Reis, Oliver; Saß, Katharina (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Kerze - Reis, Oliver; Wittke, Annika (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Beten - Meditieren - Reis, Oliver (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Segnen - Reis, Oliver (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

„Warum können wir denn jetzt nicht sagen, dass die Sophia wirklich Recht hat?“ Norm und Relativierung in religionspädagogischen Bildungsprozessen - Reis, Oliver; Roose, Hanna (Relativität und Bildung. Fachübergreifende Herausforderungen und fachspezifische Grenzen)

Religiöse Bildung als Medium der Kirchenmodernisierung und der Kirchenrestauration - Reis, Oliver; Tomberg, Markus (Aufbruch statt Rückzug. Die römisch-katholische Kirche in der Öffentlichkeit heute)

„In Erinnerung geblieben sind mir die ritualartigen Dinge“. Rituale und ihre eigensinnige Mitarbeit am nachhaltigen Lernen - Reis, Oliver; Weber, Carla (Jahrbuch für Konstruktivistische Religionsdidaktik)

Den roten Faden selbst in der Hand – Ritualisierte Selbstorganisation als Wirkungsfaktor im Paderborner Reli-Fächer - Reis, Oliver; Walter, Marie (Jahrbuch für Konstruktivistische Religionsdidaktik)

Behinderung / Inklusion - Brandstetter, Bettina; Reis, Oliver (Ethische Kernthemen. Lebensweltlich – theologisch-ethisch – didaktisch)

Akteur-Netzwerk-Theorie - Reis, Oliver (Religionsunterricht beobachten. Praktiken – Artefakte – Akteure)

Nachhaltige Wirkung von Religionsunterricht

Religionsunterricht beobachten. Praktiken – Artefakte – Akteure

Weltanschauliche, religiöse oder theologische Positionalität – Positionalität als Lösung und Problem der KJT im Zueinander von Tradition und subjektiven Überzeugungen - Reis, Oliver („Hauptsache, du hast eine Meinung und einen eigenen Glauben“ Positionalität (nicht nur) in der Kinder- und Jugendtheologie)

Acquiring religious words: Dialogical and individual construction of the word’s meaning - Viertel, Franziska; Reis, Oliver; Rohlfing, Katharina (Philosophical Transactions of the Royal Society B)

Auf die Position kommt es an?! Theologische Gespräche im Religionsunterricht und die Herausforderung der Positionalität - Reis, Oliver; Roose, Hanna (Lesepause. Magazin für alle, die im Erzbistum Paderborn Religion unterrichten)

Was meint Digitalisierung und was hat das mit dem RU zu tun? - Büttner, Gerhard; Reis, Oliver (KatBl)

Kompetenzorientiere Aufgabenformate im Distanzunterricht?! - Reis, Oliver; Woppowa, Jan (KatBl)

Der Distanzunterricht als digitalisierender Kurzschluss - Woppowa, Jan; Reis, Oliver (KatBl)

Artefakte als (An-)Zeiger der Zeit. Praxistheoretische Analysen zu religiösen Artefakten an einer Katholischen Schule - Hoyer, Isabelle; Reis, Oliver

Lernstandserhebung/-diagnostik, wissenschaftstheoretisch - Reis, Oliver (WiReLex 2/2022)

Nutritional Assessment of Ready-to-Eat Salads in German Supermarkets: Comparison of the nutriRECIPE-Index and the Nutri-Score - Schlarbaum, Laura; Forner, Frank; Bohn, Kristin; Amberg, Michael; Mäder, Patrick; Lorkowski, Stefan; Meier, Toni (Foods)
Globally, an unbalanced diet causes more deaths than any other factor. Due to a lack of knowledge, it is difficult for consumers to select healthy foods at the point of sale. Although different front-of-pack labeling schemes exist, their informative value is limited due to small sets of considered parameters and lacking information on ingredient composition. We developed and evalauated a manufacture-independent approach to quantify ingredient composition of 294 ready-to eat salads (distinguished into 73 subgroups) as test set. Nutritional quality was assessed by the nutriRECIPE-Index and compared to the Nutri-Score. The nutriRECIPE-Index comprises the calculation of energy-adjusted nutrient density of 16 desirable and three undesirable nutrients, which are weighted according to their degree of supply in the population. We show that the nutriRECIPE-Index has stronger discriminatory power compared to the Nutri-Score and discriminates as well or even better in 63 out of the 73 subgroups. This was evident in groups where seemingly similar products were compared, e.g., potato salads (Nutri-Score: C only, nutriRECIPE-Index: B, C and D). Moreover, the nutriRECIPE-Index is adjustable to any target population’s specific needs and supply situation, such as seniors, and children. Hence, a more sophisticated distinction between single food products is possible using the nutriRECIPE-Index.

E-Assessment zwischen Kompetenzorientierung und Technologieskepsis:Entwicklung eines Tools zur Messung musikalischer Fähigkeiten im Unterricht - Neuhausen, Timo (Beiträge empirischer Musikpädagogik)

Evaluation von Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Schürmann, Mirko; Liebendörfer, Michael; Büdenbender-Kuklinski, Christiane; Lankeit, Elisa; Ruge, Johanna; Schaper, Niclas; Biehler, Rolf; Hochmuth, Reinhard (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

PATTERNS 2022 The Fourteenth International Conferences on Pervasive Patterns and Applications

Effects of drawing instructions and strategic knowledge on mathematical modeling performance: Mediated by the use of the drawing strategy - Schönherr, Johanna; Schukajlow, S.; Blomberg, J.; Leopold, C. (Applied Cognitive Psychology, ac3930)

Drawing instructions, strategic knowledge, strategy-based motivation, and students' use of drawings - Schönherr, Johanna; Schukajlow, S.; Leopold, C. (Proceedings of the 45th PME Conference)

Die Kommanditistenhaftung in der GmbH & Co. KG vor Registereintragung - Eine Untersuchung auf der Grundlage Digitaler Rechtstatsachenforschung - Bartlitz, David (Neue Zeitschrift für Gesellschaftsrecht (NZG))